Making Simple Repairs: Building Your Toolbox - Mary N. Harrison (EDIS)
Every home needs some basic tools for use in simple maintenance. Remember to keep all of your tools in your toolbox. That way you can always find your tools when you need them. A simple metal box is fine. Always put your tools back in the box after using them. This document is FCS5234-01, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.